The Impact Of The Constructivist Approach On Students' Understanding Of Teaching Principles In English Learning - Tawali, Tawali (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to explore the effect of implementing a constructivist approach in English language learning on students' understanding of teaching principles. The constructivist approach, which emphasizes students' active role in constructing knowledge through social interaction, reflection, and direct experience, is expected to improve students' understanding of English teaching theories. This study used an experimental design with an experimental group receiving constructivist-based learning and a control group using traditional methods. The research sample consisted of 35 4th semester students of the English Education Study Program at Mandalika University of Education, who were selected by purposive sampling. Data were collected through written tests to measure the understanding of teaching principles, as well as questionnaires to measure students' perceptions of the application of constructivist approaches in learning. Based on the test results, there was an increase in the average pre-test score from 63 to 85 after the application of the constructivist approach, which showed a significant increase of 35%. In addition, questionnaire data showed that 78% of students felt more involved in learning after applying the constructivist approach. The collected data were analyzed using descriptive statistics and paired t-test to test for significant differences between the experimental and control groups. The results showed that the implementation of constructivist approach in English language learning has a positive influence on students' understanding of teaching principles. Students who engaged in constructivist learning experienced a significant increase in understanding compared to those who used traditional methods. The study also found that the factors of motivation and active involvement of students in learning played an important role in the successful implementation of the constructivist approach.